2017
DOI: 10.2147/ott.s129903
|View full text |Cite
|
Sign up to set email alerts
|

<sup>125</sup>I&nbsp;brachytherapy of locally advanced non-small-cell lung cancer after one cycle of first-line chemotherapy:a comparison with best supportive care

Abstract: ObjectivesThe objective of this study was to assess the efficacy of computed tomography (CT)-guided 125I brachytherapy alone in improving the survival and quality of life of patients with unresectable locally advanced non-small-cell lung cancer (NSCLC) after one cycle of first-line chemotherapy.Patients and methodsSixteen patients with locally advanced NSCLC were treated with CT-guided 125I brachytherapy after one cycle of first-line chemotherapy (group A). Sixteen patients who received only best supportive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…1A and 2C) and the rest were treated with freehand implantation. The median number of seeds implanted was 57 (range, 14-100) and the median number of needles was 5 (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Postoperative dosimetric measurements demonstrated that the actual D90 ranged between 79 and 148 Gy (mean D90, 113 Gy; Table SI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A and 2C) and the rest were treated with freehand implantation. The median number of seeds implanted was 57 (range, 14-100) and the median number of needles was 5 (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Postoperative dosimetric measurements demonstrated that the actual D90 ranged between 79 and 148 Gy (mean D90, 113 Gy; Table SI).…”
Section: Resultsmentioning
confidence: 99%
“…Surgery, external beam radiotherapy (EBRT) or chemotherapy used alone or in combination are the standard treatments recommended for patients with NSCLC (4). 125 I brachytherapy performed by implantation of 125 I radioactive seeds in the tumors can induce extensive necrosis of tumors and improve the quality of life of patients (5). Previous studies have demonstrated that iodine-125 ( 125 I) seed implantation brachytherapy exhibits good clinical results as a minimally invasive and effective treatment for a variety of tumors, such as pancreatic or liver cancer and gynecologic malignancies (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment, the caner-related symptoms of patients were obviously improved, so the ECOG performance scores were pronouncedly improved which was observed in 18 patients in our study. Song et al indicated that iodine-125 seed implantation not only showed noteworthy superiority in ameliorating cancer-related symptoms but also signi cantly improved QOL of patients diagnosed as advanced NSCLC (34). It is remarkable that the combined-modality therapy was able to signi cantly relieve cancer-related pain and improve ECOG scores which could contribute to improve QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Indications Primary lung cancer: (i) patient is not a candidate for surgery because of inferior cardiopulmonary function or advanced age 24,25 (ii) patient refused surgery; (iii) patient is not a candidate for surgery because of recurrence after surgery 22 (iv) a residual or progressive tumor is observed after surgery, radiotherapy, or chemotherapy 26 (v) thermal ablation or surgery failed to distinguish the tumor-free boundary; 27,28 (vi) Karnofsky Performance Score (KPS) > 60 and predicted life span > 6 months; and (vii) the diameter of largest tumor is < 7 cm. 12 Metastatic lung cancer: (i) the patient has ≤ 3 unilateral lesions ≤ 5 cm in diameter; (ii) if a patient has ≤ 3 bilateral lesions ≤ 5 cm in diameter, these should be treated separately.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%